2021
DOI: 10.1128/spectrum.00003-21
|View full text |Cite
|
Sign up to set email alerts
|

A Versatile Human Intestinal Organoid-Derived Epithelial Monolayer Model for the Study of Enteric Pathogens

Abstract: While traditional laboratory techniques and animal models have provided valuable knowledge in discerning virulence mechanisms of enteric pathogens, the complexity of the human gastrointestinal tract has hindered our understanding of physiologically relevant, human-specific interactions and, thus, has significantly delayed successful vaccine development. The human intestinal organoid-derived epithelial monolayer (HIODEM) model closely recapitulates the diverse cell populations of the intestine, allowing for the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 114 publications
4
52
2
Order By: Relevance
“…Recent work has shown that intestinal organoid-derived monolayers grown on permeable supports provide a physiologically relevant culture model for host-pathogen interaction, applicable to bacteria ( 21 26 , 28 ), parasites ( 27 ), and viruses ( 20 ). In this context, organoids bridge the gap between the complexity and polarized nature of the epithelium encountered in vivo and the convenient (yet sometimes misrepresentative) properties of continuous cultured cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work has shown that intestinal organoid-derived monolayers grown on permeable supports provide a physiologically relevant culture model for host-pathogen interaction, applicable to bacteria ( 21 26 , 28 ), parasites ( 27 ), and viruses ( 20 ). In this context, organoids bridge the gap between the complexity and polarized nature of the epithelium encountered in vivo and the convenient (yet sometimes misrepresentative) properties of continuous cultured cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…The latter can be accommodated by ECM-coated transwell inserts with permeable membranes of polyethylene terephthalate (PET) or similar polymers as a 2D substrate ( 18 , 19 ). Enteroid/colonoid-derived IEC layers in such transwell inserts can be efficiently cultured, differentiated, and infected by a variety of gut pathogens ( 20 28 ) but are poorly compatible with live-cell imaging. Second, nontransformed cells are difficult to manipulate genetically, which complicates introduction of fluorescent tags to visualize the host cell and its subcellular architecture by fluorescence microcopy.…”
Section: Introductionmentioning
confidence: 99%
“…Microbes (commensals, probiotics, or pathogens or their products) can be applied to the apical chambers and interact with the organoid-derived monolayers. 17 , 87 , 88 , 89 Organoid-derived monolayers can be grown within microfluidics devices that add shear forces associated with medium flow and gut wall smooth muscle stretching to the epithelial monolayer, reproducing many of the mechanical forces found in vivo , resulting in better mimicking of the epithelial monolayer differentiation. 90 , 91 , 92 Nevertheless, limitations of these systems include their cost, the need for specific handling skills, and their requirement of lots of starting materials, making experiments not always affordable by many scientists.…”
Section: The Powerful Yet Challenging Advances Brought By Organoid Mo...mentioning
confidence: 99%
“…Several studies already have provided lists of markers to check for a differentiation state of epithelial organoid cells co-cultured with nonepithelial cells (eg, intestinal organoids with cells from the enteric nervous system). 31 , 87 , 185 Selected differentiation factors can be added to the culture to promote growth of specific cells that have not been cultured successfully in vitro from stem cells (eg, Receptor activator of nuclear factor kappa-B ligand, RANKL for generating microfold cells in intestinal organoids 186 ). iPSC aggregates were shown to grow differently in the presence of different factors, other cells, or scaffolds; the core region of such structures remains very stable, while the peripheral parts respond more strongly to environmental changes.…”
Section: Outlook and Perspectivesmentioning
confidence: 99%
“…1 ). For example, Shigella , S. Typhi, and C. difficile show the highest adhesion to the large intestine ( 68 , 103 , 104 ). However, some in vitro models of these pathogen infections have been established in organoids with small intestinal properties ( 39 , 48 , 68 , 73 , 84 , 85 ).…”
Section: Points To Consider For the Proper Use Of Human Intestinal Or...mentioning
confidence: 99%